Analysis of Self-Revision In Translation Process of Analytical Exposition Text by the Third Year English Department Students of Universitas Negeri Padang - Chintya Yuliantika; Rusdi Noor Rosa (Universitas Negeri Padang, 2022)
This research was aimed to find out the types of self-revision done by the English Department students of Universitas Negeri Padang in translating an analytical exposition text from Bahasa Indonesia into English and to find out kinds of online resources used by the English Department students of Universitas Negeri Padang in doing self-revision in translating an analytical exposition text this research used a descriptive qualitative method. The participants of this study were three English Department students of Universitas Negeri Padang in academic year 2020-2021. The data in this research were the translation process collected by using Translog II and Camtasia Studio 8. The findings of this research were (1) the type of self-revision most frequently used by the students was word substitution with the frequency f 30.1% and (2) Google translate was the kind of online resources most frequently used by the students in doing self-revision in their translation process. From this research, it is concluded that self-revision has an essesntial role in the translation process.